2012
DOI: 10.5588/ijtld.11.0255
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of space-time clusters and geospatial hot spots for the occurrence of tuberculosis in Beijing

Abstract: Spatial autocorrelation and hot-spot analysis may serve as efficient tools to detect space-time clusters and geospatial hot spots of TB incidence. Between 2005 and 2009, TB incidence in Beijing showed population density and mobility-dependent and eco-social status-dependent space-time clusters and geospatial hot spots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 20 publications
8
50
0
1
Order By: Relevance
“…These results correspond with findings from Liu et al, 2012, who also detected higher TB incidence rate in the urban district of Beijing/China (1997-2001) than in other districts with lower urbanization 31 .…”
Section: Discussionsupporting
confidence: 82%
“…These results correspond with findings from Liu et al, 2012, who also detected higher TB incidence rate in the urban district of Beijing/China (1997-2001) than in other districts with lower urbanization 31 .…”
Section: Discussionsupporting
confidence: 82%
“…It is difficult to incorporate the spatial heterogeneity of the effects of ecological factors (meteorological and air pollutant factors) with those traditional methods [23,24]. In this regard, the geographic information system (GIS) is the preferred method and technique for the underlying epidemic characteristics of an infectious disease [25], which allow one to attain more easily and more efficiently data visualization and manipulation, as well as to analyse and display the geographic data [26,27,28]. However, such studies have not been conducted yet to investigate the geospatial distribution of scarlet fever in the Beijing region using GIS technology.…”
Section: Introductionmentioning
confidence: 99%
“…TB is a reemerging infectious disease and a substantial public health problem in Beijing [2], [3], the capital of the People’s Republic of China, a megacity containing many districts with large populations and high population mobility. It has been reported that the prevalence and incidence of TB is gradually becoming higher in Beijing [4], thus the prevention and control of TB is a great challenge for this city.…”
Section: Introductionmentioning
confidence: 99%